Hubungan Lama Puasa Dengan Kejadian Mual Muntah Pada Pasien Pasca Spinal Anestesi - Suhadi Suhadi; M.Hafiduddin; Anisa Rizki Julfatwiah (Jurnal Sains dan Kesehatan, 2021)
(PONV). PONV can be caused by many factors, one of which is the length of fasting. Preanesthesia fasting about 6-8 hours before surgery is performed as an effort to minimize the incidence of aspiration of stomach contents or nausea and vomiting. Objective: Determine the relationship between the length of fasting and the incidence of nausea and vomiting in post-spinal anesthesia. Research Methods: This type of research is an observational study with a Cross-sectional research design. The population in this study is all patients who will undergo spinal anesthesia in the IBS room of RSUD Kab. Batang. Sampling in this study was using the Purposive Sampling method of 49 samples and using the Spearman Rank analysis test. The research instrument uses observation sheets. Research Results: The age of most respondents in this study was 36-40 years as many as 26 respondents (53.1%), the most gender is women 32 respondents (65.3%), and those who experienced the most fasting length of 2-6 hours with 30 respondents (61,3%), while PONV as many as 29 respondents (59.2%). Based on the results of the Spearman Rank test to determine the relationship between the length of fasting and the incidence of Post Operative Nausea and Vomiting (PONV) obtained a result of 0.007 (P0.5). The majority of respondents who did not experience PONV were 14 respondents (28.6%). Conclusion: There is a significant relationship between the length of fasting and the incidence of Post Operative Nausea and Vomiting (PONV).